Association of phosphate with rhyolite glass in marine Neogene tuffs from Patagonia, Argentina. Issue 4 (1st February 2013) - Rubinstein, Nora; Fazio, Ana M.; Scasso, Roberto A.; Carey, Steven; Immenhauser, Adrian
Abstract The precipitation/replacement of Ca‐phosphate is a complex process that commonly takes place during the early diagenesis in marine sediments. The unusual occurrence of shallow marine, early diagenetic phosphatic deposits associated with glassy tuffs in the Neogene Gaiman Formation, in the Chubut Province, Patagonia, Argentina, constitutes a good case example for the study of replacement and precipitation of Ca‐phosphate on an unstable substrate. Isocon diagrams illustrate that chemical changes during glass diagenesis include gains in loss on ignition and Ca, and losses of K. These changes are the result of glass hydration during sea water–glass interaction, together with adsorption and diffusion of ions into the bulk shard; combined, these represent an incipient process of volcanic glass replacement by Ca‐phosphate. Subsequent early diagenetic P enrichment in the pore solutions led to phosphate precipitation, associated with pitting on the glass shards and pumice. The associated development of a reactive surface promoted the incorporation of P and Ca into their margins. Lastly, precipitation of calcium phosphate filled the vesicles and other open cavities, inhibiting further glass dissolution. The high porosity and reactivity of the volcanic glass provided an appropriate substrate for phosphate precipitation, leading to the development of authigenic apatite concretions in the volcanic‐glass bearing strata of the Gaiman Formation. This research is of significance for those concerned with marine phosphatic deposits and sheds light on the processes of early diagenetic phosphate precipitation by replacement of an atypical, unstable substrate like hydrated volcanic glass.